Gastric venous reconstruction to reduce gastric venous congestion after total pancreatectomy: study protocol of a single-centre prospective non-randomised observational study (IDEAL Phase 2A) - GENDER study (Gastric vENous DrainagE Reconstruction) - Mehrabi, Arianeb; Loos, Martin; Ramouz, Ali; Dooghaie Moghadam, Arash; Probst, Pascal; Nickel, Felix; Schaible, Anja; Mieth, Markus; Hackert, Thilo; Büchler, Markus W. (BMJ open, 2021)
Introduction - Total pancreatoduodenectomy (TP) is the standard surgical approach for treating extended pancreas tumours. If TP is performed with splenectomy, the left gastric vein (LGV) sometimes needs to be sacrificed for oncological or technical reasons, which can result in gastric venous congestion (GVC). GVC can lead to gastric venous infarction, which in turn causes gastric perforation with abdominal sepsis. To avoid gastric venous infarction, partial or total gastrectomy is usually performed if GVC occurs after TP. However, gastrectomy can be avoided by reconstructing the gastric venous outflow to overcome GVC and avoid gastric venous infarction. The current study aims to assess the role of gastric venous outflow reconstruction to prevent GVC after TP and avoid gastrectomy. - - Methods and analysis - In the current single-centre observational pilot study, 20 patients will be assigned to study after intraoperative evaluation of gastric venous drainage after LGV resection during TP. During surgery, on-site evaluation by the surgeon, endoscopic examination, indocyanine green, gastric venous drainage flowmetry and spectral analysis will be performed. Postoperatively, patients will receive standard post-TP care and treatment. During hospitalisation, endoscopic examination with indocyanine green will be performed on the 1st, 3rd and 7th postoperative day to evaluate gastric ischaemia. Ischaemia markers will be evaluated daily after surgery. After discharge, patients will be followed-up for 90 days, during which mortality and morbidities will be recorded. The main endpoints of the study will include, rate of GVC, rate of gastric ischaemia, rate of postpancreatectomy gastrectomy, rate of reoperation, morbidity and mortality. - - Ethics and dissemination - The study protocol has been reviewed and approved by the Ethics Committee of the University of Heidelberg. The results will be actively disseminated through peer-reviewed journals and conference presentations, and are expected in 2022. - - Trial registration number - NCT04850430.